A Super-Microsurgery Training Model: The Mouse Caudal Artery Anastomosis Model - Wu, Xue-Qiang; Liu, Hui-Ren; Yu, Zhan-Yong; Wang, Yan; Sun, Ru-Tao; Wang, Li; Gao, Yuan (Frontiers in Surgery, 2022)
Objective To establish a simple and practical model for super-microsurgery training using the middle caudal arteries of Kunming mice. Methods A ⊔-shaped incision was made approximately 1 cm from the root of the tail in the mouse, and the skin, together with the subcutaneous tissue, was turned up into a rectangular shape to the opposite side with exposure of the mouse middle caudal artery and the accompanying veins. The artery was freed for approximately 1 cm in length. The middle caudal artery was cut transversely at the site, and then the severed middle caudal artery was anastomosed end-to-end using 12-0 microsutures in the order of 6, 12, 3, and 9 o'clock with four stitches. Results The mouse caudal artery had a constant anatomical location accompanied by a vein. The immediate postoperative patency after vascular anastomosis was 100% (15/15) in all mouse models, the postoperative patency was 100% (5/5), 80% (4/5), and 75% (3/4) at 24 h, 3 days, and 1 week postoperatively, respectively. The outer diameter of the mouse middle caudal artery was 0.2 0.3 (0.22 ± 0.03) mm. The vascular anastomosis time was 6.5 15 (11.0 ± 2.5) min. Conclusion The mouse middle caudal artery was superficially located and anatomically constant, making it easy to be located and exposed. The small size of the opening made it suitable for establishing a useful model for training in super-microsurgery vascular anastomoses.